Single Level Closed Wedge Osteotomy for Bilateral Genu Valgus with Isolated Tibial Angulation Deformity: A Case Report - Saqib Yasin; Mayank Rajput; Shambhavi Rajiva; L M Gupta (Journal of Orthopaedic Case Reports)
Introduction: The term “Genu valgus” originates from the Latin “Genu” meaning Knee and “valgus” is bent outward; referring to an outward angular deformity in the knee joint which is commonly seen in children. In Genu Valgus, there is lateral deviation of the mechanical axis of the lower limb which leads to an abnormal loading force significantly affecting knee movements and maltracking of the patella. Genu valgus (femorotibial alignment) of more than 12° above 8 years of age is considered pathological and needs correction. Case Report: We report a case of a 17-year-old skeletally matured male who presented with progressive deformity in bilateral knees of 6 years duration with complaints of difficulty in walking, running, and worsening knee pain. After careful assessment, investigations, and pre-operative planning, the patient was found to have an isolated bilateral tibial origin valgus deformity with no femoral contribution to the valgus deformity; which is very rare. An individual was managed with a serial Single-level Proximal Medial Closed Wedge Osteotomy of both sides at an interval of 3 months with good correction of the deformity. At the final follow-up, the patient reported a good functional result following the corrective osteotomy. Conclusion: A Single Level Proximal Medial Tibial Closed Wedge Osteotomy is a safe and appropriate strategy to manage the rare cases of idiopathic bilateral genu valgum with tibia valga in the absence of any femoral component. Genu valgum may not always be due to distal femoral deformity.